Preoperative fasting in noncardiac surgery in a tertiary pediatric center applying European guidelines: the difficulty of giving drink to the thirsty - Zaccaria Ricci; Denise Colosimo; Francesca Donati; Luca Saccarelli; Mariateresa Pizzo; Elena Schirru; Salvatore Giacalone; Paola Serio (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Background We conducted a secondary analysis of a previously published dataset that addressed clear fluid fasting in children. The aim of this single-center, retrospective observational study conducted in a tertiary level pediatric hospital (Meyer Children’s Hospital, Florence, Italy) was to report updated results after enrollment of new patients, including clear and non-clear fluids and meals. Methods Retrospective single-center study in a tertiary pediatric hospital after the implementation of an improvement bundle. Results Overall, we enrolled 2715 patients, and after exclusion of 199 children due to incomplete data retrieval, a final cohort of 2516 subjects (1074 surgical outpatients, 981 surgical inpatients, 314 neurosurgical procedures, 147 procedures from pediatrics/oncology) was analyzed. Median age was 7.5 (3.7–12.2) years. Median (interquartile range) preoperative fasting time was 187 (119–351) min for clear fluids, 286 (218–396) min for maternal milk, 360 (285–530) min for artificial milk, 435 (350–540) min for light breakfast, and 765 (640–910) min for meal. We did not find significant differences between the clear fluid times of the previous study (1820 patients, 185 (115–340) min) and the one analyzed in the present dataset (696 patients, 192 (120–363) min) (p = 0.12). Conclusion In a pediatric hospital implementing European Society of Anesthesia recommendations for preoperative fasting, all fluids and meals are stopped very far from the scheduled times, and this notion should provide ignition for further improvement actions.